2005
DOI: 10.1093/jn/135.4.843
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Using the Food Guide Pyramid Groups Are Associated with Sociodemographic and Lifestyle Factors: The Multiethnic Cohort Study ,

Abstract: Dietary patterns have been used to identify typical combinations of foods that may be associated with disease risks. We defined dietary patterns among 195,298 participants of the Multiethnic Cohort Study in Hawaii and Los Angeles in 1993-1996. Intakes of Food Guide Pyramid groups were calculated from a quantitative FFQ for subjects of 5 ethnic groups (African Americans, Hawaiians, Japanese Americans, Latinos, and whites). Three distinct dietary patterns, "Fat and Meat," "Vegetables," and "Fruit and Milk," were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
114
4
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(152 citation statements)
references
References 34 publications
28
114
4
6
Order By: Relevance
“…Further, our findings are in accordance with several studies that have shown 'Western'-type dietary patterns to be followed more by younger individuals (30,(46)(47)(48)(49) . This may reflect acculturation to Western and/or urbanized eating habits and departure from traditional dietary habits (50) to a more modern and convenient dietary pattern mainly by younger generations.…”
Section: Discussionsupporting
confidence: 93%
“…Further, our findings are in accordance with several studies that have shown 'Western'-type dietary patterns to be followed more by younger individuals (30,(46)(47)(48)(49) . This may reflect acculturation to Western and/or urbanized eating habits and departure from traditional dietary habits (50) to a more modern and convenient dietary pattern mainly by younger generations.…”
Section: Discussionsupporting
confidence: 93%
“…The three dietary patterns identified in the present study were similar to the dietary patterns found by previous studies conducted among Asian and Western populations using factor analysis (10,14,15,22) .…”
Section: Discussionsupporting
confidence: 88%
“…The Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA) population survey of 976 men aged 45-64 years also found a negative association of smoking status (P , 0?001) with a healthy dietary pattern (31) . (14) . Consistent with these findings, another study has shown that smokers are less likely than non-smokers to consume vegetables and milk or dairy foods.…”
Section: Discussionmentioning
confidence: 99%
“…A healthy dietary pattern has been consistently associated with a higher socioeconomic position (Dynesen et al, 2003;Huot et al, 2004;Robinson et al, 2004;Park et al, 2005;Kant and Graubard, 2007).…”
Section: Introductionmentioning
confidence: 99%